Marine Chemistry - Brightwell, Chris (T.F.H. Publications, 2007)
In Marine Chemistry, CR Brightwell draws from his years of aquatic experience and provides a comprehensive guide to preparing and maintaining proper water parameters in marine aquaria for his fellow hobbyists. Its contents- from basic to advanced issues- are written clearly and are easily accessible by anyone, from the inexperienced novice to the seasoned veteran. Accompanied by brilliant photography, this valuable and authoritative source of information is sure to be the cornerstone of any hobbyists library